Hypertension among Young Adults in the Shopping Malls of Kathmandu - Shakya, S; Timilsina, M; Timilsina, K; Lamsal, M; Dhakal, S; Neupane, P (Nepalese Heart Journal, 2013)
Background Hypertension is a major public health challenge in the world. Developing countries share the major burden of it. Unlike thought before, hypertension is increasing among poor, young and women. Methods It was a cross sectional study carried out in The Hypertension Screening and Awareness Program conducted in the shopping malls at the heart of Kathmandu on the occasion of World Hypertension Day 2012 by Shahid Gangalal National Heart Center, Kathmandu. The blood pressure was measured according to World Heart Organization’s guideline by registered nurses. There were total 486 participants with the mean age of 29.51±10.77years. Majority of the participants were male (67.1%). Most of the participants were less or equal to 40 years (84.6%). Mean systolic blood pressure was 112.3±14.69mmHg and mean diastolic blood pressure was 75.09±11.89 mmHg. Average mean blood pressure was 87.41±12.28mmHg in the study population. Results Despite majority of participants were at young age, prevalence of hypertension was 23.7%, pre-hypertension was 30% and 46.3% had ideal blood pressure according to JNC-7 Classification. Prevalence of hypertension was higher among male (30.39% vs. 10%). Almost two third of the hypertensive subjects were less or equal to 40 years (64.35%). Awareness, treatment and control of hypertension were 39.13%, 18.26% and 7.38% respectively. Conclusion In conclusion, Hypertension is an emerging public health challenge in urban areas of Nepal. Most importantly, it may be increasing among young population. Moreover, awareness, treatment and control rates are not satisfactory. DOI: http://dx.doi.org/10.3126/njh.v9i1.8346 Nepalese Heart Journal Vol.9(1) 2012 pp.33-36